Tindak Tutur Ilokusi Ekspresif dr. Tirta pada Podcast Malaka - Sistyani Putri Utami; Eko Suroso; Eko Muharudin; Laily Nurlina (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2026)
This study discusses the expressive illocutionary speech acts used by Dr. Tirta in the Malaka podcast entitled